Implementation of Digital Village in Totobo Village, Pomalaa District, Kolaka Regency - Septiana, Anis Ribcalia; Nento, Lukiyanto; MZ, Ahmad Farouq (Journal of Public Representative and Society Provision, 2025)
The purpose of this study is to find out how the implementation of Digital Village is in Totobo Village, Pomala District, Kolaka Regency. In the research conducted by the author using a Qualitative Research Method with a Descriptive Approach and Qualitative Case Study Research Type. The location of the research is in Totobo Village, Pomalaa District, Kolaka Regency. Informants in this study include the Village Apparatus and the Totobo Village Community. In collecting data, the author conducted Observations, Interviews and Documentation, which were then analyzed by reducing data, presenting data, then drawing conclusions in data analysis were also carried out when collecting data. Digital village is a concept that integrates the use of Information and Communication Technology in various aspects. In a study conducted by the Author in Totobo Village, Pomalaa District, Kolaka Regency, it was found that the implementation of Digital Village in terms of Communication, Resources, Disposition, Bureaucratic Structure has been going well but not yet fully optimal. The community, which previously received information manually, has been facilitated by the use of Digital media, in this case social media as a medium for delivering Village Information. The obstacles found were related to the network, Servers that hinder application access, Village Webs that have not been realized as a resource for information facilities related to village profiles and information that are needed and can be accessed by the public, there has been no Socialization of Digital-based Public Services to the community as a means of helping the community understand and use digital technology effectively.